(untitled) (University Journal of Zoology, Rajshahi University, 2009)
Indirect application was used to assay the toxicity of five insecticides; viz. malathion, carbosulfan, cymbush, imidacloprid and azadirachtin against four important crop infesting aphid species, Aphis craccivora Koch, Aphis gossypii Glover, Myzus persicae (Sulzer) and Lipaphis erysimi (Kaltenbach), reared on bean, brinjal, potato and cauliflower plants respectively. Residual film technique was applied by bringing leaves with tested aphids of the vegetable plants in the laboratory. Malathion was the least toxic to all aphids having LC50 as 327.97, 333.92, 305.26 and 313.77 Î¼g cm-2 for A. craccivora, A. gossypii, M. persicae and M. persicae respectively. Cypermethrin was the most toxic showing LC50 as 12.55, 12.29, 12.55 and 12.10 Î¼g cm-2 in the above mentioned species of aphid respectively. Carbosulfan and imidacloprid showed moderate toxicity. Azadirachtin as a natural plant origin insecticide proved to be the most toxic having LC50 as 0.41 Î¼g cm-2 for A. craccivora, 0.34 Î¼g cm-2 for A. gossypii and 0.44 Î¼g cm-2 for both M. persicae and L. erysimi. Key words: Insecticide, toxicity, azadirachtin, Aphis craccivora, Aphis gossypii, Myzus persicae, Lipaphis erysimi Â doi:10.3329/ujzru.v27i0.1950 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 31-34